Progress in cryptology - INDOCRYPT 2018 : 19th International Conference on Cryptology in India, New Delhi, India, December 9-12, 2018, Proceedings /: 19th International Conference on Cryptology in India, New Delhi, India, December 9-12, 2018, Proceedings. ([2018]) - Unknown
No abstract available